A plenitude humana e o cuidado integral na perspectiva de Viktor Frankl - Lima, Maria Eugênia Calheiros de (2012)
The general intention of this article was to understand the concept of human being in the thought of Viktor Frankl. In particular, the aims were to study the anthropological and philosophical foundations of his thinking about the man, research the meaning of his Experimentum Crucis, and also clarify his Dimensional Ontology. The study used a qualitative methodology in existential phenomenological perspective, involving bibliographical research into those writings of Frankl and some of his principal interpreters which are relevant to the theme. The Critelli s analytical method was employed in seeking to understand Frankl s Experimentum Crucis. Conclusions reveal Augustinian and Thomist philosophical elements in Viktor Frankl's conception of "human fulfillment as self-transcendence, as well as shows strong influences of Max Scheler's axiology and Martin Heidegger's fundamental ontology. However, despite the influence of a range of authors with diverse epistemological perspectives, this study reveals the originality and internal unity of Frankl s thought about human